Analisis Faktor-Faktor Yang Mempengaruhi Kemiskinan di Provinsi Jambi (Jurnal Simki Economic, 2023)
Local government policies are expected to overcome poverty problems in their regions. Regional development policies are aimed at overcoming the problem of poverty because poverty is an important problem that needs to be solved to support the success of economic development. This research is intended to determine the factors that influence poverty in Jambi Province, so that the results of this study can be used as a reference for the government to adopt policies in efforts to develop and improve the welfare of the people of Jambi Province. The research data uses secondary data obtained from sources from the Central Statistics Agency (BPS) from 2009 to 2019. The method used is a case study because this research consists of collecting data that supports one event raised. The tools used are inductive statistics and panel data regression. The results showed that the population variable had a positive and insignificant effect on the poverty rate, the unemployment variable had a negative but not significant effect on poverty, the economic growth variable had a negative and significant effect on poverty and the education variable had a positive and insignificant effect on poverty in Jambi Province in 2009 -2019.